Japanese students contributing to a pro-verbalisation pedagogy - Bao, Dat; Shachter, Jonathan (Neofilolog, 2024)
Investigating the perspectives of three individual Japanese learners of English from a university in Japan on the nature of their classroom reticence, this project highlights the voices of silent learners who yearn to speak. Unfortunately, silent student perspectives often go unheard in the classroom and are under-reported in research studies. We intended to search out these silent ‘pro-talk’ voices and investigate conditions that might assist these students in (a) moving away from reticence, (b) increasing verbal communication, and (c) developing their verbal English proficiency. Drawn from in-depth interview data and to contribute to English language teaching (ELT) pedagogy, the following article outlines strategic ways of assisting the learning of quiet students who do not wish to be silent anymore. Although, in their ideology, these students yearn for a verbally proactive classroom process, they often experience verbal limitations in the everyday classroom. While on the outside, these students seem to be peacefully quiet, within each, there is an accumulation of feelings and thoughts that cause internal tension and, at times, intense disappointment. For this study, we have labelled these silent students as ‘pro-verbalisation learners’. Speaking entirely in Japanese, the three pro-verbalisation learners in this study shared critical views toward undesirable classroom processes and offered possible solutions to improve limitations in existing classroom methods. According to these students, ideal conditions for verbal change can only occur if the teacher is willing to modify their pedagogy to establish new participation rules, ease classroom tension, nurture peer cohesiveness, and build verbally supportive elements into the learning process.